Real interest rate parity: Decomposition of financial and comercial components in the case of Colombia - Clavijo, Sergio (Estudios Económicos de El Colegio de México, 1996)
The concept of interest rate parity is here revisited, emphasizing the different results that are obtained when the analysis is made either using a nominal interest rate difference, adjusted by the actual or expected rate of depreciation, or using a real interest rate difference. The results vary according to deviations from "purchasing power parity".